A zinc-based double-flow battery structure and application

By setting a settlement tank and filter in the negative electrode frame of the zinc-based flow battery, the problem of zinc block falling off and blocking the electrolyte flow channel is solved, the battery performance and cycle life are improved, and the electrolyte flow stability and zinc are achieved The effectiveness of block storage.

CN118919759BActive Publication Date: 2025-01-10DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411407805.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

During the circulation process, due to insufficient adhesion of zinc elemental materials, the zinc block falls off and blocks the electrolyte flow channel, increasing flow resistance, which leads to attenuation and failure of the battery performance.

Method used

A zinc-based dual-flow battery structure is designed, using a settlement tank and a filter net in the negative electrode frame. The settlement tank is used to store fallen zinc blocks, and the filter net is used to block the zinc blocks from entering the electrolyte flow channel to ensure electrolysis. Liquid flow, improving battery performance and cycle life.

Benefits of technology

It effectively reduces the impact of zinc blocking flow channels, improves battery performance and cycle life, and the reasonable setting of the volume of settlement tank and the porosity of the filter screen can maintain battery performance and prevent zinc blocking and electrolyte flow from being blocked.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118919759B_ABST
    Figure CN118919759B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of liquid flow battery energy storage, and specifically relates to a zinc-based dual-liquid flow battery structure and application. A single cell mainly includes a negative electrode frame, a diaphragm, and a positive electrode frame stacked in sequence; the electrode frame is respectively a circular rectangular flat plate with a through hole in the middle, and grooves serving as an electrolyte inlet flow channel and an electrolyte outlet flow channel are respectively provided on the surface of one side of the flat plate close to the diaphragm and on the opposite sides of the through hole; a groove serving as a sedimentation tank is provided on the surface of one side of the negative electrode frame close to the diaphragm, between the electrolyte outlet flow channel and the middle through hole, and the electrolyte in the middle through hole flows out of the negative electrode frame through the electrolyte outlet flow channel after passing through the sedimentation tank. The present invention provides a sedimentation tank between the electrolyte outlet flow channel of the negative electrode frame and the carbon felt electrode, which can reduce the increase in battery flow resistance caused by zinc blocks blocking the flow channel due to the shedding of negative zinc, and the influence of electrolyte flow obstruction, thereby improving the performance and cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of liquid flow battery energy storage, and in particular relates to a zinc-based double-liquid flow battery structure and application. Background Art

[0002] Zinc-based liquid flow battery is a low-cost, high-safety liquid flow battery energy storage technology. The negative electrode of the zinc-based liquid flow battery is a deposition and dissolution reaction of zinc. During charging, zinc ions are converted into zinc elemental substances and attached to the carbon felt electrode; during discharge, zinc elemental substances are converted into zinc ions. Due to the insufficient adhesion of zinc elemental substances on the carbon felt electrode, as the number of battery cycles increases, zinc elemental substances will gradually fall off the carbon felt electrode, flow into the flow channel with the flow of electrolyte, and block the electrolyte flow channel. As zinc blocks accumulate in the flow channel, the battery flow resistance gradually increases, resulting in insufficient electrolyte flow, insufficient supply of active substances, and increased battery polarization; more seriously, when the zinc blocks completely block the electrolyte flow channel, the electrolyte cannot flow into or out of the battery, causing the battery to fail completely. Summary of the invention

[0003] In order to solve the above technical problems, the purpose of the present invention is to provide a zinc-based liquid flow battery structure.

[0004] To achieve the above object, the present invention adopts the following technical solutions:

[0005] A zinc-based double-flow battery structure is a single cell or a battery pack composed of two or more single cells connected in series, wherein the single cell mainly comprises a sequentially stacked annular negative electrode frame with a through hole in the middle for accommodating an electrode, a diaphragm, and an annular positive electrode frame with a through hole in the middle for accommodating an electrode; and a negative carbon felt electrode placed in the middle through hole of the annular negative electrode frame and an annular positive carbon felt electrode placed in the middle through hole of the positive electrode frame;

[0006] The negative electrode frame and the positive electrode frame are respectively annular rectangular plates with a through hole in the middle, and grooves serving as an electrolyte inlet flow channel and an electrolyte outlet flow channel are respectively provided on the surface of the plate on one side close to the diaphragm and on the opposite sides of the through hole (i.e., the upper and lower sides of the surface); through holes are provided at the ends of the grooves of the electrolyte inlet flow channel and the electrolyte outlet flow channel (the end away from the through hole in the middle of the plate), which are used for the electrolyte to flow into or out of the flow channels of the inlet and outlet electrolyte flow channel grooves respectively;

[0007] A groove as a sedimentation tank is provided on the surface of one side of the negative electrode frame close to the diaphragm, between the electrolyte outlet flow channel and the middle through hole. The electrolyte in the middle through hole flows out of the negative electrode frame through the sedimentation tank and then through the electrolyte outlet flow channel. The sedimentation tank is used to store the zinc blocks falling off the carbon felt, and the bottom plate of the sedimentation tank plays the role of insulating the zinc blocks and the bipolar plates.

[0008] A filter screen is arranged between the sedimentation tank and the adjacent part of the electrolyte outlet flow channel, which is arranged perpendicularly to the surface of the plate, and is used to prevent the zinc block from being washed into the electrolyte flow channel groove by the electrolyte; preferably, it is arranged perpendicularly to the bottom surface of the electrolyte outlet flow channel groove (fixed on the bottom surface of the electrolyte outlet flow channel groove) and the height is the depth of the groove, and is used to prevent the zinc block from being washed into the electrolyte flow channel groove by the electrolyte; or, it is perpendicular to the surface of the plate and arranged in the sedimentation tank near the electrolyte outlet flow channel side, and the height is the depth of the sedimentation tank to prevent the zinc block from being washed into the electrolyte flow channel groove by the electrolyte; the porosity of the filter screen is 40%-60% (preferably 45%-55%), and the pore size is 0.1mm-1mm (preferably 0.5mm-0.8mm);

[0009] The cross section of the sedimentation tank parallel to the surface of the negative electrode frame plate is a trapezoid, and is gradually contracted and reduced along the width direction parallel to the surface of the negative electrode frame plate (that is, the side close to the middle through hole is a longer lower bottom side, and the side close to the electrolyte outlet flow channel is a shorter upper bottom side), so that the electrolyte is accelerated at this position to prevent the flow of the electrolyte from being blocked by the setting of the filter screen; the cross-sectional area of ​​the intersection of the sedimentation tank and the electrolyte outlet flow channel perpendicular to the surface of the negative electrode frame plate (or the length of the upper bottom side of the trapezoid) is the ratio of the cross-sectional area of ​​the intersection of the sedimentation tank and the middle through hole of the negative electrode frame perpendicular to the surface of the negative electrode frame plate (or the length of the lower bottom side of the trapezoid) to the cross-sectional area of ​​the intersection of the sedimentation tank and the middle through hole of the negative electrode frame perpendicular to the surface of the negative electrode frame plate (or the length of the lower bottom side of the trapezoid), and the contraction ratio is between 0.5-0.8 (preferably 0.6-0.7);

[0010] The thickness of the negative electrode frame is 4mm-6mm (preferably 4.5mm-5.5mm), and the thickness of the carbon felt is 5mm-7mm (preferably 5.5mm-6.5mm). The original thickness of the carbon felt is higher than the thickness of the electrode frame. After the stack is assembled, the carbon felt is compressed to the same thickness as the electrode frame.

[0011] The depth of the grooves of the electrolyte inlet and outlet flow channels is 1mm-3mm (preferably 2mm-3mm), and the depth of the sedimentation tank is 2mm-5mm (preferably 3mm-4mm), which must be greater than the depth of the electrolyte flow channel groove, and the two form a stepped structure;

[0012] The width of the sedimentation tank from the middle through hole to the electrolyte outlet flow channel is 5%-10% (preferably 7-9%) of the length of the carbon felt electrode along the electrolyte flow direction;

[0013] During the charging and discharging process of a single battery or a battery pack composed of two or more single batteries connected in series, the negative electrode frame is assembled into a battery and placed in a direction parallel to the flat surface and the horizontal plane. The placement direction of the battery is ensured to be placed horizontally with the horizontal plane, which helps the zinc block to settle better in the sedimentation tank;

[0014] The electrolyte inlet flow channel and the electrolyte outlet flow channel of the positive electrode frame are directly connected to the middle through hole, and no sedimentation tank is provided;

[0015] The beneficial effects of the present invention are as follows:

[0016] The zinc-based liquid flow battery structure provided by the present invention has a sedimentation tank disposed between the electrolyte outlet flow channel of the negative electrode frame and the carbon felt electrode, which can reduce the increase in battery flow resistance caused by zinc blocks blocking the flow channel due to the shedding of negative zinc, and the influence of electrolyte flow obstruction, thereby improving the performance and cycle life of the battery. The larger the volume of the sedimentation tank, the stronger its ability to store zinc blocks, and the higher the performance retention rate of the battery, but its volume cannot be infinitely enlarged because it will occupy the effective area of ​​the carbon felt electrode and affect the battery performance. Therefore, the setting of the sedimentation tank should take these two factors into consideration. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.

[0018] Figure 1 The negative electrode frame structure of the zinc-based liquid flow battery of the present invention. 1 is the electrolyte inlet flow channel groove, 2 is the electrolyte outlet flow channel groove, 3 is the middle through hole, and 4 is the sedimentation tank;

[0019] Figure 2 The positive electrode frame structure of the zinc-based flow battery of the present invention is shown in FIG. 1 is the electrolyte inlet flow channel groove, 2 is the electrolyte outlet flow channel groove, and 3 is the middle through hole;

[0020] Figure 3 The cross section of the interface between the sedimentation tank and the electrolyte outlet flow channel groove in the negative electrode frame of the zinc-based liquid flow battery provided by the present invention, wherein 1 is the thickness of the sedimentation tank bottom plate, 2 is the filter screen, which is also the cross section of the electrolyte outlet flow channel groove; the overall thickness is the electrode frame thickness. DETAILED DESCRIPTION

[0021] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.

[0022] The embodiment of the present invention is a zinc-based double-flow battery structure, which is a single cell. The single cell mainly includes a sequentially stacked annular negative electrode frame with a through hole in the middle for accommodating an electrode, a diaphragm, and an annular positive electrode frame with a through hole in the middle for accommodating an electrode; and a negative carbon felt electrode placed in the middle through hole of the annular negative electrode frame and an annular positive carbon felt electrode placed in the middle through hole of the positive electrode frame;

[0023] The negative electrode frame and the positive electrode frame are respectively annular rectangular plates with a through hole in the middle, and grooves serving as an electrolyte inlet flow channel and an electrolyte outlet flow channel are respectively provided on the surface of the plate on one side close to the diaphragm and on the opposite sides of the through hole (i.e., the upper and lower sides of the surface); through holes are provided at the ends of the grooves of the electrolyte inlet flow channel and the electrolyte outlet flow channel (the end away from the through hole in the middle of the plate), which are used for the electrolyte to flow into or out of the flow channels of the inlet and outlet electrolyte flow channel grooves respectively;

[0024] A groove as a sedimentation tank is provided on the surface of one side of the negative electrode frame close to the diaphragm, between the electrolyte outlet flow channel and the middle through hole. The electrolyte in the middle through hole flows out of the negative electrode frame through the sedimentation tank and then through the electrolyte outlet flow channel. The sedimentation tank is used to store the zinc blocks falling off the carbon felt, and the bottom plate of the sedimentation tank plays the role of insulating the zinc blocks and the bipolar plates.

[0025] A filter screen is arranged between the sedimentation tank and the electrolyte outlet flow channel; the filter screen is perpendicular to the surface of the plate, arranged in the sedimentation tank near the electrolyte outlet flow channel, and has a height equal to the depth of the sedimentation tank, and is used to prevent the zinc block from being washed into the electrolyte flow channel groove by the electrolyte; the porosity of the filter screen is 40%-60% (preferably 45%-55%), and the pore size is 0.1mm-1mm (preferably 0.5mm-0.8mm);

[0026] The cross section of the sedimentation tank parallel to the surface of the negative electrode frame plate is a trapezoid, and is gradually contracted and reduced along the width direction parallel to the surface of the negative electrode frame plate (that is, the side close to the middle through hole is a longer lower bottom side, and the side close to the electrolyte outlet flow channel is a shorter upper bottom side), so that the electrolyte is accelerated at this position to prevent the flow of the electrolyte from being blocked by the setting of the filter screen; the cross-sectional area of ​​the intersection of the sedimentation tank and the electrolyte outlet flow channel perpendicular to the surface of the negative electrode frame plate (or the length of the upper bottom side of the trapezoid) is the ratio of the cross-sectional area of ​​the intersection of the sedimentation tank and the middle through hole of the negative electrode frame perpendicular to the surface of the negative electrode frame plate (or the length of the lower bottom side of the trapezoid) to the cross-sectional area of ​​the intersection of the sedimentation tank and the middle through hole of the negative electrode frame perpendicular to the surface of the negative electrode frame plate (or the length of the lower bottom side of the trapezoid), and the contraction ratio is between 0.5-0.8 (preferably 0.6-0.7);

[0027] The thickness of the negative electrode frame is 4mm-6mm (preferably 4.5mm-5.5mm), and the thickness of the carbon felt is 5mm-7mm (preferably 5.5mm-6.5mm). The original thickness of the carbon felt is higher than the thickness of the electrode frame. After the stack is assembled, the carbon felt is compressed to the same thickness as the electrode frame.

[0028] The depth of the grooves of the electrolyte inlet and outlet flow channels is 1mm-3mm (preferably 2mm-3mm), and the depth of the sedimentation tank is 2mm-5mm (preferably 3mm-4mm), which must be greater than the depth of the electrolyte flow channel groove, and the two form a stepped structure;

[0029] The width of the sedimentation tank from the middle through hole to the electrolyte outlet flow channel is 5%-10% (preferably 7-9%) of the length of the carbon felt electrode along the electrolyte flow direction;

[0030] The negative electrode frame is assembled into a battery in such a way that its flat surface is parallel to the horizontal plane. The battery is placed in a direction parallel to the horizontal plane, which helps the zinc block settle better in the sedimentation tank.

[0031] The electrolyte inlet flow channel and the electrolyte outlet flow channel of the positive electrode frame are directly connected to the middle through hole, and no sedimentation tank is provided;

[0032] Assemble zinc-bromine double flow battery for battery testing. The positive and negative electrolytes are 2mol / L zinc bromide solution, 3mol / L potassium chloride solution and 0.4mol / L MEP (scientific name: 1-methyl-1-ethylpyrrolidine bromide) complexing agent aqueous solution. The diaphragm is a commercial Daramic porous diaphragm; the rectangular negative carbon felt electrode and positive carbon felt electrode area are: length * width = 40 * 20 cm 2 , 800 cm 2 The electrolyte flows along the length direction.

[0033] Comparative Example 1

[0034] Comparative Example 1 uses a traditional electrode frame structure to assemble a zinc-bromine flow battery. The thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 2 mm, the negative electrode frame is not provided with a sedimentation tank and a filter structure, the carbon felt electrode is adjacent to the electrolyte flow channel groove, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0035] Number of battery stacks: 20;

[0036] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0037] Battery cycle performance: Coulomb efficiency 86.2%, voltage efficiency 81.9%, energy efficiency 70.6%;

[0038] The number of cycles at which the battery energy efficiency decays by 10%: 104;

[0039] Comparative Example 1 used a traditional electrode frame structure to assemble a zinc-bromine flow battery. As the number of cycles increased, zinc shedding became more obvious, resulting in poor battery performance and serious performance degradation. After 104 cycles, the battery energy efficiency decayed by 10%.

[0040] Comparative Example 2

[0041] Comparative Example 2 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 2 mm, the depth of the sedimentation tank is 4 mm, no filter is provided, the shrinkage ratio of the sedimentation tank is 0.6, and the width of the sedimentation tank is 8% of the length of the carbon felt electrode along the electrolyte flow direction; the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0042] Number of battery stacks: 20;

[0043] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0044] Battery cycle performance: Coulomb efficiency 87.5%, voltage efficiency 82.1%, energy efficiency 71.8%;

[0045] The number of cycles for battery energy efficiency to decay by 10%: 128;

[0046] Comparative Example 2 adopts the electrode frame structure provided by the present invention, but because no filter is provided at the electrolyte outlet flow channel, the zinc blocks settled in the sedimentation tank are washed into the electrolyte flow channel by the electrolyte, causing the battery to fail.

[0047] Comparative Example 3

[0048] Comparative Example 3 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 2 mm, the depth of the sedimentation tank is 4 mm, the porosity of the filter is 90%, the pore size is 0.5 mm, the shrinkage ratio of the sedimentation tank is 0.6, the width of the sedimentation tank is 8% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0049] Number of battery stacks: 20;

[0050] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0051] Battery cycle performance: Coulomb efficiency 90.5%, voltage efficiency 82.8%, energy efficiency 74.9%;

[0052] The number of cycles at which the battery energy efficiency decays by 10%: 218;

[0053] The porosity of the filter in the electrode frame described in Comparative Example 3 is too large, resulting in negligible filtering effect of the filter. As the battery cycles, the zinc blocks fall off and block the flow channel, causing the battery to fail.

[0054] Comparative Example 4

[0055] Comparative Example 4 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 2 mm, the depth of the sedimentation tank is 4 mm, the porosity of the filter is 10%, the pore size is 0.5 mm, the shrinkage ratio of the sedimentation tank is 0.6, the width of the sedimentation tank is 8% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0056] Number of battery stacks: 20;

[0057] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0058] Battery cycle performance: Coulomb efficiency 86.5%, voltage efficiency 78.8%, energy efficiency 68.2%;

[0059] The number of cycles at which the battery energy efficiency decays by 10%: 224;

[0060] The porosity of the filter in the electrode frame described in Example 4 is too small. Although it can block the zinc block from flowing into the electrolyte flow channel, it also hinders the flow of the electrolyte, and the voltage efficiency of the battery is low.

[0061] Comparative Example 5

[0062] Comparative Example 5 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 2 mm, the depth of the sedimentation tank is 4 mm, the porosity of the filter is 50%, the pore size is 0.5 mm, the shrinkage ratio of the sedimentation tank is 0.1, the width of the sedimentation tank is 8% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0063] Number of battery stacks: 20;

[0064] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0065] Battery cycle performance: Coulomb efficiency 86.7%, voltage efficiency 75.8%, energy efficiency 65.7%;

[0066] The number of cycles at which the battery energy efficiency decays by 10%: 217;

[0067] The shrinkage ratio of the sedimentation tank in the electrode frame described in Example 5 is too small. Although it can have a significant accelerating effect on the electrolyte, the cross-sectional area of ​​the sedimentation tank and the electrolyte outlet flow channel is too low, which affects the flow area of ​​the electrolyte and hinders the flow of the electrolyte, resulting in lower battery efficiency.

[0068] Comparative Example 6

[0069] Comparative Example 6 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 2 mm, the porosity of the filter is 50%, the pore size is 0.5 mm, no sedimentation tank structure is provided, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0070] Number of battery stacks: 20;

[0071] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0072] Battery cycle performance: Coulomb efficiency 82.5%, voltage efficiency 76.8%, energy efficiency 63.4%;

[0073] The number of cycles at which the battery energy efficiency decays by 10%: 97;

[0074] No sedimentation tank structure is provided in the electrode frame described in Example 6, and the carbon felt electrode fits tightly with the filter screen and the electrolyte outlet flow channel. Since there is no sedimentation tank to store the detached zinc blocks, the zinc element generated on the carbon felt gradually grows into zinc dendrites and gradually grows into the electrolyte flow channel. Even if there is a filter screen, it still cannot prevent the zinc dendrites from growing into the flow channel, which eventually leads to battery failure.

[0075] Comparative Example 7

[0076] Comparative Example 7 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 2 mm, the depth of the sedimentation tank is 4 mm, the porosity of the filter is 50%, the pore size is 0.5 mm, the shrinkage ratio of the sedimentation tank is 0.6, the width of the sedimentation tank is 8% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 90°, and the specific parameters of the battery stack are as follows:

[0077] Number of battery stacks: 20;

[0078] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0079] Battery cycle performance: Coulomb efficiency 85.8%, voltage efficiency 79.3%, energy efficiency 68.0%;

[0080] The number of cycles at which the battery energy efficiency decays by 10%: 322;

[0081] The battery is placed vertically to the horizontal plane, which reduces the effect of the sedimentation tank in the electrode frame. The zinc blocks cannot be in the sedimentation tank and can only be isolated by the filter. The ability to block the zinc blocks is reduced, resulting in the battery failing due to blockage after a certain number of cycles.

[0082] Example 1

[0083] Example 1 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 2 mm, the depth of the sedimentation tank is 4 mm, the porosity of the filter is 50%, the pore size is 0.5 mm, the shrinkage ratio of the sedimentation tank is 0.8, the width of the sedimentation tank is 8% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0084] Number of battery stacks: 20;

[0085] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0086] Battery cycle performance: Coulomb efficiency 93.1%, voltage efficiency 85.2%, energy efficiency 79.3%;

[0087] The number of cycles at which the battery energy efficiency decays by 10%: 459;

[0088] Example 1 adopts the electrode frame structure provided by the present invention. Due to the presence of the negative electrode frame sedimentation tank and the filter screen, the phenomenon of the detached zinc blocks blocking the flow channel is effectively suppressed, and the battery performance and cycle stability are greatly improved compared with the control example.

[0089] Example 2

[0090] Example 2 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 2 mm, the depth of the sedimentation tank is 4 mm, the porosity of the filter is 50%, the pore size is 0.5 mm, the shrinkage ratio of the sedimentation tank is 0.6, the width of the sedimentation tank is 8% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0091] Number of battery stacks: 20;

[0092] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0093] Battery cycle performance: Coulomb efficiency 94.8%, voltage efficiency 85.3%, energy efficiency 80.9%;

[0094] The number of cycles at which the battery energy efficiency decays by 10%: 988;

[0095] In Example 2, the shrinkage ratio of the sedimentation tank is further reduced, that is, the flow capacity of the electrolyte is improved. It can be seen that the coulombic efficiency and voltage efficiency of the battery are significantly improved. After the battery runs for 788 cycles, the energy efficiency is only attenuated by 10%.

[0096] Example 3

[0097] Example 3 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 3 mm, the depth of the sedimentation tank is 5 mm, the porosity of the filter is 50%, the pore size is 0.5 mm, the shrinkage ratio of the sedimentation tank is 0.6, the width of the sedimentation tank is 8% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0098] Number of battery stacks: 20;

[0099] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0100] Battery cycle performance: Coulomb efficiency 94.9%, voltage efficiency 86.7%, energy efficiency 82.3%;

[0101] The number of cycles at which the battery energy efficiency decays by 10%: 897;

[0102] Compared with Example 2, Example 3 increases the depth of the electrolyte flow channel, and the flow rate of the electrolyte in the carbon felt is improved. It can be seen that the performance of the battery is improved compared with that of Example 2, and the filter and the sedimentation tank can effectively prevent the zinc block from flowing into the electrolyte flow channel, and the battery cycle performance retention rate is maintained.

[0103] Example 4

[0104] Example 4 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 6 mm, the thickness of the carbon felt is 7 mm, the depth of the electrolyte flow channel groove is 1 mm, the depth of the sedimentation tank is 2 mm, the porosity of the filter is 40%, the pore size is 0.1 mm, the shrinkage ratio of the sedimentation tank is 0.8, the width of the sedimentation tank is 5% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0105] Number of battery stacks: 20;

[0106] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0107] Battery cycle performance: Coulomb efficiency 93.1%, voltage efficiency 83.7%, energy efficiency 77.9%;

[0108] The number of cycles at which the battery energy efficiency decays by 10%: 502;

[0109] In this embodiment, parameters such as the thickness of the electrode frame, the thickness of the carbon felt, the flow channel grooves, the depth of the sedimentation tank, the porosity and pore size of the filter screen are changed, and the battery still has good cycle performance.

[0110] Example 5

[0111] Example 5 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 4 mm, the thickness of the carbon felt is 5 mm, the depth of the electrolyte flow channel groove is 1 mm, the depth of the sedimentation tank is 2 mm, the porosity of the filter is 60%, the pore size is 1 mm, the shrinkage ratio of the sedimentation tank is 0.8, the width of the sedimentation tank is 10% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0112] Number of battery stacks: 20;

[0113] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0114] Battery cycle performance: Coulomb efficiency 92.4%, voltage efficiency 82.8%, energy efficiency 76.5%;

[0115] The number of cycles at which the battery energy efficiency decays by 10% is 493.

[0116] In this embodiment, parameters such as the thickness of the electrode frame, the thickness of the carbon felt, the flow channel grooves, the depth of the sedimentation tank, the porosity and pore size of the filter screen are changed, and the battery still has good cycle performance.

[0117] Example 6

[0118] Example 6 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 2 mm, the depth of the sedimentation tank is 4 mm, the porosity of the filter is 50%, the pore size is 0.5 mm, the shrinkage ratio of the sedimentation tank is 0.5, the width of the sedimentation tank is 8% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0119] Number of battery stacks: 20;

[0120] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0121] Battery cycle performance: Coulomb efficiency 93.8%, voltage efficiency 83.7%, energy efficiency 78.5%;

[0122] Number of cycles for battery energy efficiency to decay by 10%: 378.

[0123] Compared with Example 2, as the shrinkage ratio of the settling tank further decreases, the acceleration capacity of the electrolyte decreases, the battery flow resistance increases, and the battery energy efficiency decreases, but it is still significantly better than the comparative example.

[0124] Example 7

[0125] Example 7 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 2 mm, the depth of the sedimentation tank is 4 mm, the porosity of the filter is 50%, the pore size is 0.5 mm, the shrinkage ratio of the sedimentation tank is 0.7, the width of the sedimentation tank is 8% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0126] Number of battery stacks: 20;

[0127] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0128] Battery cycle performance: Coulomb efficiency 94.2%, voltage efficiency 85.7%, energy efficiency 80.7%;

[0129] The number of cycles at which the battery energy efficiency decays by 10%: 874;

[0130] Compared with Example 1, Example 7 reduces the shrinkage ratio of the sedimentation tank to 0.7. Although the acceleration ability of the electrolyte is weakened, the flow area of ​​the electrolyte is increased, and the flow resistance of the battery is reduced. The efficiency and cycle stability of the battery are better than those in Example 1.

[0131] Example 8

[0132] Example 8 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 2 mm, the depth of the sedimentation tank is 4 mm, the porosity of the filter is 50%, the pore size is 0.5 mm, the shrinkage ratio of the sedimentation tank is 0.8, the width of the sedimentation tank is 10% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0133] Number of battery stacks: 20;

[0134] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0135] Battery cycle performance: Coulomb efficiency 93.4%, voltage efficiency 83.9%, energy efficiency 78.4%;

[0136] The number of cycles at which the battery energy efficiency decays by 10%: 602;

[0137] In Example 8, compared with Example 1, the width of the sedimentation tank is increased. Although the sedimentation tank can store more zinc blocks, the flow resistance of the battery is increased and the voltage efficiency is reduced.

[0138] Example 9

[0139] Example 9 adopts the electrode frame structure provided by the present invention, wherein the thickness of the negative electrode frame is 5 mm, the thickness of the carbon felt is 6 mm, the depth of the electrolyte flow channel groove is 1 mm, the depth of the sedimentation tank is 4 mm, the porosity of the filter is 50%, the pore size is 0.5 mm, the shrinkage ratio of the sedimentation tank is 0.8, the width of the sedimentation tank is 8% of the length of the carbon felt electrode along the electrolyte flow direction, the placement direction of the battery and the angle between its flat surface and the horizontal plane are 0°, and the specific parameters of the battery stack are as follows:

[0140] Number of battery stacks: 20;

[0141] Current density: 40 mA / cm 2 , Charging time: 3 hours, Discharge cut-off voltage: 16V;

[0142] Battery cycle performance: Coulomb efficiency 95.2%, voltage efficiency 83.7%, energy efficiency 79.7%;

[0143] The number of cycles at which the battery energy efficiency decays by 10%: 878;

[0144] Compared with Example 1, in Example 9, the depth of the electrolyte flow channel groove is reduced, and the zinc block storage capacity of the sedimentation tank is improved. However, due to the increase in flow resistance of the flow channel, the voltage efficiency of the battery is reduced, but its cycle stability is better than that of Example 1.

[0145] It can be concluded from the comparative examples and the embodiments that the electrode frame structure provided by the present invention is adopted, and since the negative electrode frame is provided with a sedimentation tank and a filter screen structure, it can store the zinc blocks that fall off and prevent the phenomenon that the zinc blocks block the flow channel as the electrolyte flows, thereby improving the battery performance and cycle performance. In addition, the porosity of the filter screen determines the ability to prevent the zinc blocks from flowing into the electrolyte flow channel. The appropriate porosity can effectively prevent the zinc blocks from flowing into the electrolyte flow channel and blocking the flow channel, but its porosity cannot be too low, which will also hinder the flow of the electrolyte and reduce the battery performance. In addition, the cross-sectional contraction ratio of the sedimentation tank plays a secondary acceleration role for the electrolyte. If the contraction ratio is too large, the cross-sectional area of ​​the electrolyte flow channel is too small, which will affect the flow of the electrolyte. If the contraction ratio is too small, the acceleration effect on the electrolyte is not obvious, so the contraction ratio of the sedimentation tank is also set appropriately.

Claims

1. A zinc-based double-flow battery structure, which is a single cell or a battery pack composed of two or more single cells connected in series, wherein the single cell mainly comprises a sequentially stacked annular negative electrode frame with a through hole in the middle for accommodating an electrode, a diaphragm, and an annular positive electrode frame with a through hole in the middle for accommodating an electrode; and a negative carbon felt electrode placed in the middle through hole of the annular negative electrode frame and an annular positive carbon felt electrode placed in the middle through hole of the positive electrode frame; The negative electrode frame and the positive electrode frame are respectively annular rectangular plates with a through hole in the middle, and grooves serving as an electrolyte inlet flow channel and an electrolyte outlet flow channel are respectively provided on the surface of one side of the plate close to the diaphragm and on two opposite sides of the through hole; through holes are provided at the ends of the grooves of the electrolyte inlet flow channel and the electrolyte outlet flow channel, respectively used for the electrolyte to flow into or out of the flow channels of the inlet and outlet electrolyte flow channel grooves; Features: A groove as a sedimentation tank is provided on the surface of one side of the negative electrode frame close to the diaphragm, between the electrolyte outlet flow channel and the middle through hole, and the electrolyte in the middle through hole flows out of the negative electrode frame through the electrolyte outlet flow channel after passing through the sedimentation tank; A filter screen is arranged between the sedimentation tank and the electrolyte outlet flow channel, and is arranged vertically to the surface of the plate; the porosity of the filter screen is 40%-60%, and the pore size is 0.1mm-1mm; The cross-section of the sedimentation tank parallel to the surface of the negative electrode frame plate is trapezoidal, and is gradually contracted along the width direction parallel to the surface of the negative electrode frame plate, that is, the side close to the middle through hole is the longer lower bottom side, and the side close to the electrolyte outlet flow channel is the shorter upper bottom side; the ratio of the cross-sectional area of ​​the junction of the sedimentation tank and the electrolyte outlet flow channel perpendicular to the surface of the negative electrode frame plate to the cross-sectional area of ​​the junction of the sedimentation tank and the middle through hole of the negative electrode frame perpendicular to the surface of the negative electrode frame plate is the contraction ratio of the sedimentation tank, and the contraction ratio is between 0.5-0.

8.

2. The zinc-based double-flow battery structure according to claim 1, characterized in that: The filter screen is arranged on the bottom surface of the electrolyte outlet flow channel groove and is arranged perpendicular to the bottom surface of the groove, and the height is the depth of the groove; Alternatively, the filter screen is perpendicular to the surface of the flat plate and is disposed in the sedimentation tank near the electrolyte outlet flow channel, with a height equal to the depth of the sedimentation tank.

3. The zinc-based double-flow battery structure according to claim 1, characterized in that: The thickness of the negative electrode frame is 4mm-6mm, and the thickness of the carbon felt is 5mm-7mm. The original thickness of the carbon felt is higher than the thickness of the electrode frame. After the battery stack is assembled, the carbon felt is compressed to the same thickness as the electrode frame.

4. The zinc-based double-flow battery structure according to claim 1, characterized in that: The depths of the grooves at the inlet and outlet of the electrolyte flow channel are 1mm-3mm respectively, and the depth of the sedimentation tank is 2mm-5mm, which must be ensured to be greater than the depth of the groove of the electrolyte flow channel, and the two form a stepped structure.

5. The zinc-based dual-flow battery structure according to claim 1, characterized in that: The width of the sedimentation tank from the middle through hole to the electrolyte outlet flow channel is 5%-10% of the length of the carbon felt electrode along the electrolyte flow direction.

6. An application of the zinc-based dual-flow battery structure according to any one of claims 1 to 5, characterized in that: During the charging and discharging process of a single battery or a battery pack consisting of two or more single batteries connected in series, The negative electrode frame is assembled into a battery and placed in the following direction during use: its flat surface is placed parallel to the horizontal plane. The placement direction of the battery ensures that it is placed horizontally with the horizontal plane, which helps the zinc block to settle better in the sedimentation tank.

7. The application of the zinc-based double-flow battery structure according to claim 6, characterized in that: The electrolyte inlet flow channel and the electrolyte outlet flow channel of the positive electrode frame are directly connected to the middle through hole, and no sedimentation tank is provided.

Citation Information

Patent Citations

  • Split type bipolar plate structure of flow battery and electric pile

    CN219303710U